Applying Raked Wingtips in Sailplane Design - Yu, Haoyang (International Journal of Mechanical and Electrical Engineering, 2026)
Raked wingtips are widely used on passenger aircraft, but their potential application for low-speed aircraft such as sailplanes is less explored. Since wingtip treatments like winglets are commonly used on sailplanes, a raked wingtip can also be an alternative. In this study, the aerodynamic efficiency increase resulting from applying a raked wingtip to high-aspect-ratio sailplane wings, as well as the effectiveness of modern lifting line theory in optimizing the wingtip treatment design, were investigated. By conducting Reynolds-Averaged Navier-Stokes (RANS) Computational Fluid Dynamics (CFD) simulations on a GPU, the optimal raked wingtip configuration with a 25-degree leading-edge sweep angle was determined. The performance of the optimized raked wingtip is also compared with the baseline wing, baseline wing with a potential optimal winglet, and an extended wing. The results show that the optimal raked wingtip can improve the lift-to-drag ratio by nearly 2%, while the improvement of the selected winglet is only about 0.5%. Visualization of the flow field indicates that both the raked wingtip and the winglet can reduce the wingtip vortex. However, although the winglet can redirect the flow at the wingtip, the corner generates interference drag. Furthermore, the modern lifting line theory (implemented on the MachUpX program) was applied to optimize the raked wingtip and the winglet. For the raked wingtip, this theory can predict the general trend of the lift coefficient versus the sweep angle, but is unreliable in predicting the drag. For the winglet, the optimization effectiveness is limited due to its failure to simulate the complex 3D effect. The findings suggest that the raked wingtip is promising for sailplane applications, while also providing a general guideline for using modern lifting line theory to optimize raked wingtip and winglet design.